Water-sediment regulation drives stage-specific microbial shifts and network complexity in the Yellow River reservoir-river continuum - Zhang, Yanmin; Zhao, Bo; Gui, Zewei; Zhang, Man; Gao, Xiaofei; Chang, Xulu; Yang, Guokun; Meng, Xiaolin; Jiang, Hongchen (Frontiers in Microbiology, 2025)
High-turbidity rivers, exemplified by the Yellow River, face significant ecological risks due to anthropogenic water-sediment regulation (WSR), which disrupts sedimentary habitats and biogeochemical cycles. However, the stage-specific impacts of WSR on microbial community structure, network complexity, and biogeochemical functions in reservoir-river continua remain poorly understood. In this study, we investigated microbial responses across different WSR stages in the Xiaolangdi Dam reservoir-river continuum using an integrated approach, including 16S rRNA gene sequencing, molecular ecological network analysis (MENs), and hierarchical partitioning. The results showed that WSR induced transient but profound shifts in microbial communities. The sediment-regulation stage (Inter_WSR3) exerted the strongest disturbance, characterized by peak turbidity (77.80 NTU), nutrient fluxes (NO3− = 3.10 mg/L), and sediment resuspension, which restructured surface sediment (SS) communities dominated by copiotrophic Gammaproteobacteria (35.69%) and Bacteroidia (14.82%). Microbial α-diversity transiently increased during WSR but recovered to baseline levels post-disturbance, masking β-diversity divergence driven by niche differentiation. Molecular ecological networks exhibited peak complexity (nodes = 1,318; modularity = 0.73) during Inter_WSR3 but failed to recover Post_WSR, reflecting weakened functional redundancy and ecosystem resilience. Hierarchical partitioning identified stage-specific drivers: chlorophyll a (Chla) dominated SS assembly during Inter_WSR3, while nitrate (NO₃−) and turbidity governed particle-attached (PA) and free-living (FL) communities. Light limitation and sediment-water interactions overrode dissolved oxygen and temperature as primary drivers in the Yellow River. These findings reveal that WSR disrupts microbial co-occurrence patterns and functional redundancy, with lasting consequences for ecosystem services. To reconcile sediment management with ecological sustainability, we advocate phased WSR implementation, targeted monitoring of FL/PA communities, and habitat restoration to enhance connectivity. This study advances the mechanistic understanding of high-turbidity river ecology and provides actionable insights for global river management.